2023
DOI: 10.3389/fmicb.2023.1170790
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of codon bias in 13 Ganoderma mitochondrial genomes

Abstract: IntroductionCodon usage bias is a prevalent phenomenon observed across various species and genes. However, the specific attributes of codon usage in the mitochondrial genome of Ganoderma species remain unknown.MethodsIn this study, we investigated the codon bias of 12 mitochondrial core protein-coding genes (PCGs) in 9 Ganoderma species, including 13 Ganoderma strains.ResultsThe codons of all Ganoderma strains showed a preference for ending in A/T. Additionally, correlations between codon base composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 119 publications
2
4
0
Order By: Relevance
“…The result was similar to the study in Salvia o cinalis [53], Leucaena trichandra [54] and Pereskia aculeata [55]. The nad4 gene possessed 39 potential RNA editing sites and was the most edited of pomegranate mitogenome, which was supported by other studies [14,39].…”
Section: Rna Editing Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The result was similar to the study in Salvia o cinalis [53], Leucaena trichandra [54] and Pereskia aculeata [55]. The nad4 gene possessed 39 potential RNA editing sites and was the most edited of pomegranate mitogenome, which was supported by other studies [14,39].…”
Section: Rna Editing Analysissupporting
confidence: 90%
“…Codon usage preference is usually considered to be the result of the tendency to develop relative equilibrium within cells during species evolution, and codons with a RSCU greater than 1 are considered to be used by amino acid preference [17,[37][38][39]. The result indicated that Phe, Ile and Glu were the most common amino acids, and Met and Ter were much less common in the P. granatum mitogenome.…”
Section: Identi Cation Of Condon Usage and Repeat Sequencesmentioning
confidence: 99%
“…The result was similar to the study in Salvia officinalis [ 55 ], Leucaena trichandra [ 56 ] and Pereskia aculeata [ 57 ]. The nad4 gene possessed 39 potential RNA editing sites and was the most edited of pomegranate mitogenome, which was supported by other studies [ 14 , 41 ].…”
Section: Discussionsupporting
confidence: 77%
“…Codon usage preference is usually considered to be the result of the tendency to develop relative equilibrium within cells during species evolution, and codons with a RSCU greater than 1 are considered to be used by amino acid preference [ 17 , 39 41 ]. The result indicated that Phe, Ile and Glu were the most common amino acids, and Met and Ter were much less common in the P. granatum mitogenome.…”
Section: Discussionmentioning
confidence: 99%
“…At present, CUB analyses based on plant genomes are highly available due to the extensive sequencing of nuclei and organellar genomes, leading to valid and credible results [ 4 , 15 ]. Accumulating advances based on the genomes revealed that several factors, in particular natural selection, played a significant role in CUB [ 10 , 16 , 17 ]. Conversely, the significance of CUB in gene families has not been well studied.…”
Section: Introductionmentioning
confidence: 99%